Estudos de íons de terras raras em matrizes vítreas para aplicações em termometria óptica - Bernardino, Filippe de Carvalho (2018)
Accurate temperature monitoring allows to know and to control many processes from a wide variety of technological areas. Temperature sensors use of physical properties changes to provide thermal system information. It can be classified as Thermocouples; Resistance thermometers; Thermistors; Silicon sensors and Optical or radiation thermometers. Optical thermometers have been widely used due to the need for sensing with high resolution and wide working ranges. These have high sensitivity beyond no need contact with the monitored body. These features enable optical thermometers to be useful in medical, biological applications or in applications requiring high wear resistance. Studies of vitreous matrices doped TR shown excellent results in optical thermometry, especially when it applied together with the Fluorescence Intensity Ratio (FIR) technique of thermally coupled energy levels. This technique allows the monitoring of the temperature reducing considerably electromagnetic interferences of the system or oscillations coming from the sensor radiative emissions. This work carried out a study of the optical properties of borosilicate and phosphate vitreous matrices doped with concentrations of 0.5w%, 1.0w% and 3.0w% of Eu3+ and Er3+ ions, as a function of temperature. It was observed that matrices with greater asymmetry degree, presented better results of thermal sensitivity. The thermally coupled levels studied were 2S3/2 and 2H11/2 and show better values of relative sensitivity to matrices with lower Er3+ concentrations with values close to 4.47 %K-1 for SBP, indicating that the reabsorption process, due to íons proximity, influences negatively on the thermometric characteristics. For phosphate doped with 1.0% Er3+ show a 5.31 %K-1 thermal sensitivity value. For Eu3+ doped matrices glasses, tested in the biological temperature ranges, the fluorescences involving 5D0 → 4F2 (700 nm) heat-coupled energy levels under excitation at 576 nm and 614 nm were studied. For the doped SBP matrices with higher concentration of ions, wa found a values of 1.29% K-1 of sensitivity and the value of 1.25% K-1 were present for the sample of phosphate matrix doped 1.0% Eu3+. The higher degree of covalence and symmetry between the ions, reduces the sensitivity values.